2021
DOI: 10.3390/nu13020360
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone in Pregnancy: Vitamin D and Other Determinants

Abstract: We aimed to assess the parathyroid hormone (PTH) concentration in pregnant women at the beginning of pregnancy (1st trimester) and within days before delivery (3rd trimester) and evaluate its determinants. From September 2014 through December 2015 in a cross-sectional study, 204 women in the 1st trimester of pregnancy and 203 women in the 3rd trimester of pregnancy were recruited. Blood samples were collected to measure PTH and circulating 25-hydroxy-vitamin D (25(OH)D) concentrations. Lifestyle and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
(96 reference statements)
1
15
0
Order By: Relevance
“…In our analysis, a significant impact of calcium and vitamin D intake on PTH concentration was not demonstrated. However, varying effects of dietary and supplemental calcium intake on PTH concentration are described previously [8,9]. The dietary or supplemental intake did not affect PTH among healthy, Caucasian pregnant women from Ireland [8].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In our analysis, a significant impact of calcium and vitamin D intake on PTH concentration was not demonstrated. However, varying effects of dietary and supplemental calcium intake on PTH concentration are described previously [8,9]. The dietary or supplemental intake did not affect PTH among healthy, Caucasian pregnant women from Ireland [8].…”
Section: Discussionmentioning
confidence: 79%
“…postmenopausal women reported that calcium intake (1000mg/day) and vitamin D intake (1000IU/day) suppressed PTH significantly; still, neither calcium nor vitamin D supplements alone suppressed serum PTH [9]. The mixed results could be attributed to a lack of homogeneity and design errors.…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…In addition, PTHrP produces the relaxation of the smooth muscles of the uterus and stimulates cell growth and differentiation. In humans, the concentration of PTHrP in the blood increases throughout pregnancy, and its levels correlate with the calcium concentration [ 31 , 32 ].…”
Section: Pthrp Adipose Tissue and Pregnancymentioning
confidence: 99%
“…Studies in normal pregnancies have demonstrated that median PTH serum concentrations are statistically lower in early pregnancy compared to late pregnancy, while PTH-rP and corrected calcium levels are significantly higher in pregnant women than in nonpregnant women [6,7]. Furthermore, it has been demonstrated that type 2 diabetics presented higher serum PTH-rP levels than control subjects, and PTH-rP induces insulin expression in pancreatic β-cells [8,9].…”
Section: Introductionmentioning
confidence: 99%